1979
DOI: 10.1007/bf02671479
|View full text |Cite
|
Sign up to set email alerts
|

Two food applications of cottonseed flours and meals

Abstract: Procedures for preparing texturized cottonseed protein and isolate. In either case the free gossypol is effectively reduced. Further work is in progress especially on cottonseed protein isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…() also found PHE, LEU, and LYS as the most predominate essential amino acids in glandless cottonseeds. Other authors found a similar concentration of LYS (3.6 g/100 g of protein) in cottonseed (De Buckle et al., ). The concentration of PHE, LEU, and LYS found in GCSM is comparable to soy protein (Gorinstein et al., ).…”
Section: Resultsmentioning
confidence: 56%
“…() also found PHE, LEU, and LYS as the most predominate essential amino acids in glandless cottonseeds. Other authors found a similar concentration of LYS (3.6 g/100 g of protein) in cottonseed (De Buckle et al., ). The concentration of PHE, LEU, and LYS found in GCSM is comparable to soy protein (Gorinstein et al., ).…”
Section: Resultsmentioning
confidence: 56%
“…Samples with only 5% CSM have the highest EI. Other results show extruded CSM with EI ranging from 1.1 -1.5 [40,54]. Other authors also obtained similar EI with corn or wheat flour complemented with bean proteins or soybean flour, respectively [53,54].…”
Section: Expansion Index (Ei)mentioning
confidence: 60%
“…Other results show extruded CSM with EI ranging from 1.1 -1.5 [40,54]. Other authors also obtained similar EI with corn or wheat flour complemented with bean proteins or soybean flour, respectively [53,54]. Changes in extrudate functional properties such as EI are due to structural starch transformations [55][56][57].…”
Section: Expansion Index (Ei)mentioning
confidence: 73%
“…A method was reported for the preparation of cottonseed protein isolate (CSPI) using meal from commercial expeller press-solvent extraction (De. Buckle et al, 1979). Wan et al (1995), in another study, employed alternate solvents for gossypol removal from cottonseeds, which posed a lower health risk than hexane.…”
Section: Chemical Methods For the Degossypolization Of Csmmentioning
confidence: 99%
“…Spadaro et al (1979) reviewed numerous food applications of CSP concentrate, including meat products (such as beef burgers, meatballs, fresh sausages and frankfurters), extruded cereal-type products (such as snacks and textured vegetable proteins), and baked goods (such as cookies, doughnuts, cakes and breads). De Buckle et al (1979) also reported that cottonseed flours could be texturized in a way similar to that of soybean flour, simultaneously reducing the free gossypol content to safe levels. The same authors also produced a CSPI with 90% protein, which had a white creamy colour and a bland flavour.…”
Section: Food Applications Of Cottonseed Meal (Csm) and Cottonseed Pr...mentioning
confidence: 99%